The Influence of the La3+ Content on the Mechanical Properties of Electrooptic Transducers Based on PLZT Type Ceramics - CZERWIEC, Marek; BRZEZIŃSKA, Dagmara; ZACHARIASZ, Radosław; ILCZUK, Jan (Archives of Acoustics, 2008)
Modification of the PZT system by the addition La3+ ions has marked beneficial effect on several the basic parameters, such as squerness of the hysteresis loop, decreased coercive filed, increased dielectric constant, maximum coupling coefficients, increased mechanical compliance, decreased Tc temperature, and enhanced optical transparency. The mechanical and electrical properties in lanthanum modified lead zirconate-titanate ceramics of 5/50/50 and 10/50/50 were studied by internal friction Q¡1, dynamic Young modulus E, electric permittivity " and tangent of dielectric loss of angle tan± measurements. The temperature dependences of Q¡1 = f(T) and E = f(T) were determinated in temperature range from 300 K to 600 K. The temperature dependences of " = f(T) and tan± = f(T) were determinated in temperature range from 300 K to 730 K. The values of TC obtained during " and tan± measurements were respectively: 560 K for 5/50/50 and 419 K for 10/50/50.